Language Error Patterns in Indonesian Teacher Education: The Impact of Digital Communication on Academic Language Use - Kartolo, Rahmat; Nofasari, Erlinda; Harahap, Dedek Afrida; Susanti, Dewi; Sibarani, Asni (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Indonesian language functions as the primary medium of academic communication in higher education, yet language errors persist among university students. This study investigated the forms, frequencies, and causal factors of language errors among Indonesian Language and Literature Education students at STKIP Budidaya Binjai. Employing qualitative descriptive methodology, the research collected data from 20 students in semesters III and V through systematic observation, semi-structured interviews, and documentary analysis of over 200 written samples during a 14-week period. Results revealed five error categories with varying frequencies: non-standard words (38%), code mixing (25%), ineffective sentences (15%), spelling errors (12%), and morphological errors (10%). Analysis demonstrated substantial contextual variation, with digital communication platforms showing significantly higher error rates than formal academic contexts. Primary causal factors included informal language habits reinforced through peer interaction, pervasive social media influence, and insufficient emphasis on formal register maintenance. The findings indicate that students possess greater linguistic competency than aggregate error rates suggest but demonstrate selective application of standard forms based on perceived formality requirements. This research contributes empirical evidence for developing targeted pedagogical interventions including explicit register instruction, vocabulary formality training, and structured language development activities to enhance communicative competence among prospective educators in Indonesian teacher education contexts.